First maturity assessment and allometric growth of skipjack tuna, Katsuwonus pelamis (Linnaeus, 1758), landed at Ternate Island - Susanto, Adi Noman; Lumingas, Lawrence J.L (Graduate Program of Sam Ratulangi University, 2014)
Title (Bahasa Indonesia): Pendugaan pertama matang kelamin dan pertumbuhan alometri ikan cakalang, Katsuwonus pelamis (Linnaeus, 1758), yang didaratkan di Pulau Ternate Skipjack tuna, Katsuwonus pelamis (Linnaeus, 1758), is a very important species for Indonesian fisheries. A total of 462 specimens (254 males and 208 females) collected from fish landings in Ternate Island from November 2013 to April 2014 were used to estimate length at first sexual maturity, length-weight relationship, and length-head circumference relationship. The length at first sexual maturity (FL50) was 489.68 mm. The length-weight relationship equations were W = 0.0001*FL2.7232 for males and W = 0.0002*FL2.6595 for females, respectively. Student’s t-test indicated significant deviation of ‘b’ from ‘3’ towards negative allometric growth (p< 0.05). The length-head circumference relationship equations were HC = 0.5453*FL1.0263for males and HC = 0.6519*FL0.9985for females, respectively. Student’s t-test indicated no significant deviation of ‘b’ from ‘1’ towards isometric growth (p> 0.05). Analysis of covariance showed that there was no significant difference between sexes (p> 0.05) for both relationships. Hence, a common length-weight relationship and a common length-head circumference relationship can be derived using pooled data of both sexes. Ikan cakalang, Katsuwonus pelamis (Linnaeus, 1758) merupakan spesies yang sangat penting untuk perikanan Indonesia. Sejumlah 462 spesimen (254 jantan dan 208 betina) ikan cakalang yang diperoleh dari ikan yang didaratkan di Pulau Ternate, selama periode November 2013 sampai April 2014 telah digunakan untuk menduga panjang matang kelamin pertama, hubungan panjang-berat, dan hubungan panjang-keliling lingkar kepala. Panjang pada saat matang kelamin pertama (PC50) adalah 489,68 mm. Persamaan hubungan panjang-berat diperoleh BT = 0,0001*PC2,7232 untuk jantan dan BT = 0,0002*PC2,6595 untuk betina. Hasil uji-t Student menunjukkan penyimpangan yang nyata ‘b’ dari ‘3’ cenderung ke arah pertumbuhan alometrik negatif (p < 0,05). Persamaan hubungan panjang-keliling lingkar kepala diperoleh LK = 0,5453*PC1,0263 untuk jantan dan LK = 0,6519*PC0,9985 untuk betina. Hasil uji-t Student menunjukkan deviasi yang tidak nyata nilai ‘b’ dari ‘1’ yang cenderung ke arah pertumbuhan isometrik (p > 0,05). Analisis kovarians menunjukkan bahwa tidak terdapat perbedaan yang nyata antara jantan dan betina (p > 0,05) untuk kedua hubungan tersebut di atas. Oleh karena itu, suatu hubungan panjang-berat umum dan suatu hubungan panjang-lingkar kepala umum dapat dibuat dengan menggunakan data gabungan kedua jenis kelamin.